King Lear : Cambridge School Shakespeare - William Shakespeare (U.K. Cambridge University Press, 2009)
This new edition of King Lear is part of the established Cambridge School Shakespeare series and has been substantially updated with new and revised activities throughout. Remaining faithful to the series' active approach, it treats the play as a script to be acted, explored and enjoyed. As well as the complete script of King Lear, you will find a variety of classroom-tested activities, an eight-page colour section and an enlarged selection of notes including information on characters, performance, history and language.
Keywords: Play, Drama; Play -- Play; Drama -- Drama